Pendampingan Guru Sekolah Dasar Dalam Pelaksanaan Pembelajaran Berdiferensiasi pada Komunitas Belajar Kelompok Kerja Guru Di Kota Palangka Raya: Assistance for Elementary School Teachers in the Implementation of Differentiated Learning in the Teacher Working Group Learning Community in the City of Palangka Raya - Eshariyani, Eshariyani; Ernawatie, Ernawatie; Berliani, Teti; Sumarnie, Sumarnie; Nugroho, Piter Joko; Limin, Dagai L; Aprianto, Aprianto; Purnomo, Widiharto; Winaryo, Slamet; Radiafilsan, Christian; Sedek, Melky (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
To support Indonesia's educational vision, and as part of efforts to restore learning, the Merdeka Curriculum was developed as a curriculum framework that is more flexible, while also focusing on essential material and developing students' character and competencies. Through the application of differentiated learning, students will not only be able to maximize their potential, but they can also learn about various important life values ​​that will contribute to their development in a more holistic or complete manner. Differentiated learning is learning that is rooted in meeting the needs of students both in terms of learning readiness, interest, or learning profile and how the teacher responds to these learning needs. This community service activity is carried out with the aim of providing assistance and guidance to teachers, especially at the elementary school level so that they can develop differentiated learning and its application in the classroom, so that student-centered learning activities can be carried out properly. The method of implementing community service activities is carried out by: (1) theoretical socialization related to differentiated learning for teachers; (2) workshops on the application of differentiated learning; and (3) assistance and guidance in organizing differentiated learning in the classroom based on the Freedom to Learn curriculum. The results of this PkM activity are: (1) teachers gain additional knowledge related to differentiated learning; (2) teachers can prepare Differentiated Learning Implementation Plans; and (3) teachers are capable of carrying out differentiated learning at all grade levels, especially at the elementary school level.